2015
DOI: 10.1016/j.meddos.2014.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of testicular dose delivered by intensity-modulated radiation therapy (IMRT) and volumetric-modulated arc therapy (VMAT) in patients with prostate cancer

Abstract: Introduction A small decrease in testosterone has been documented after prostate irradiation, possibly due to incidental dose to the testes. Testicular dose from prostate external beam radiation plans with either IMRT or VMAT were calculated to investigate any difference. Methods Testicles were contoured for 16 patients being treated for localized prostate cancer. Two plans were created for each patient, one with IMRT and one with VMAT. No specific attempt was made to reduce testicular dose. Minimum, maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although stereotactic body radiation therapy (SBRT) has been recognized as a standard treatment option for lowand intermediate-risk prostate cancer, 1,2 concerns regarding the sequelae of hypofractionation remain. [3][4][5] The proximity and radiosensitivity of the testes raises concern for reduced testicular function and impaired quality of life after SBRT. 6 The impact of conventionally fractionated radiation therapy on testosterone levels is itself unclear, with reports of posteradiation therapy testosterone ranging from insignificantly changed 7,8 to transiently depressed 9,10 and even permanently decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Although stereotactic body radiation therapy (SBRT) has been recognized as a standard treatment option for lowand intermediate-risk prostate cancer, 1,2 concerns regarding the sequelae of hypofractionation remain. [3][4][5] The proximity and radiosensitivity of the testes raises concern for reduced testicular function and impaired quality of life after SBRT. 6 The impact of conventionally fractionated radiation therapy on testosterone levels is itself unclear, with reports of posteradiation therapy testosterone ranging from insignificantly changed 7,8 to transiently depressed 9,10 and even permanently decreased.…”
Section: Introductionmentioning
confidence: 99%
“…The possible reasons were the dosimeter has been moved or the testicles have been in different position during the treatment session [16]. Various studies have shown that the distance of the testicles from the lower border of the radiation field is the most important factor affecting testicular dose [8,14,[17][18][19]. Herman, et al showed that the percentage of the dose testicles received due to the scattered radiation is inversely proportional to the distance of the testicles from the lower border of the radiation field [8].…”
Section: Discussionmentioning
confidence: 99%
“…In the study performed by Martin et al ., among 12 cases of prostate cancer, the mean dose delivered with VMAT was higher than the dose delivered with IMRT. The difference was 4.3 Gy ( p = 0.019) and was statistically significant [ 38 ].…”
Section: Technical Radiotherapy Developmentsmentioning
confidence: 99%